Pengaruh Promosi Jabatan Dan Mutasi Terhadap Motivasi Kerja Karyawan/Ti Di Divisi SDM PT PSP - Yussi Rapareni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This research aims to determine how the influence of job promotions on work motivation, how the influence of mutations on work motivation, and how the influence of job promotions and mutations on employee motivation in HR Division of PT Sriwidjaja Palembang Fertilizer. This research was conducted by distributing questionnaires online to employees in HR Division of PT Sriwidjaja Palembang Fertilizer. The questionnaire contains of 45 (fourty five) statements, where each variable consists of 15 (fifteen) statements. The number of samples in this study were 50 respondents. The data used primary and secondary data. After the data obtained, an analysis was carried out using quantitative and qualitative descriptive analysis. The analytical tool used SPSS version 23. The results of this research were the promotion has a significant effect on employee motivation. This was illustrated by the rejection of H1 and the acceptance of Ho and a significant value of X1 of 0.014 <0.05, which meant that promotion of position (X1) significantly influenced work motivation (Y). In addition, the results also obtained that mutations has a significant effect on employee work motivation. This was illustrated by rejecting Ho1 and accepting Ho, and a significant X2 value of 0,000 <0.05 meant that mutation (X2) significantly influenced work motivation (Y). The test results showed that the t-count value for mutation variable (X2) was 4.725, while the value of t table with a significant level of 0.05 (5%), and df = n-k- 1 = 50-2-1 = 47 is 2.011. As for simultaneously, promotion (X1) and mutation (X2) significantly influenced work motivation (Y). This could be seen from the results of the F test, which known that a significant value of 0,000, which meant sig. F (0,000) <0.05. This showed that the independent variable has a strong influence on the dependent variable. Based on the results of the coefficient of determination, 0.591 meant that 59.1% of the Promotion variable of Position and Mutation (the independent variable) could be explained by the variable of work motivation (the dependent variable), while the remaining 40.9% was influenced by other factors not included in this research.